PENGARUH LARUTAN ASAM LAKTAT DAN SALIVA BUATAN TERHADAP ION FLUOR WATER SETTABLE GIC - Yudha Gilang Saputra; Isyana Erlita; Agung Satria Wardhana (Dentin, 2022)
ABSTRACTBackground: Secondary caries is a caries lesion that starts at the margin of the restoration, it is influenced by the salivary flow rate. Conventional GIC materials are easily soluble in salivary flow so thar Water Settable GIC is a solution for dentist in terms of practicality and strength as the latest restorative material. Objectives: To analyze the effect of lactic acid and artificial saliva on the releasw of fluoride ion Water Settable GIC. Methods: Forty-eight specimens (diameter 5 mm x thickness 2 mm; n = 8 / group) were made with Water Settable GIC. Samples that met the criteria were divided into 6 groups. Samples were        immersed for 1 and 7 days in an incubator in 37oC temperature. For control group aquadest used to immerse the samples. The levels of fluoride ion release were read using a UV-VIS spectrophotometer. The data obtained were tested using the SPSS application. Results: The One-Way Anova parametric test results of day one and seven (p<0,05). The Bonferonni Post Hoc test showed that there was a significant difference between all treatment groups lactic acid day 1 (10,505 ± 0,285), lactic acid day 7 (11,609 ± 0,202), artificial saliva day 1 (4,639 ± 0,227), artificial saliva day 7 (8,273 ± 0,184), aquadest day 1 (3,286 ± 0,475), aquades day 7 (5,778 ± 0,823). Conclusion: There is an effect of lactic acid and artificial saliva on fluoride ion from Water Settable GIC. Keyword: Aquadest, Artificial saliva, Lactic acid, Release of ion fluoride, Water Settable GIC. ABSTRAK Latar Belakang: Karies sekunder adalah lesi karies yang dimulai dari tepi restorasi. Hal ini dipengaruhi oleh kecepatan aliran saliva. Bahan GIC konvensional mudah larut dalam aliran saliva, sehingga Water Settable GIC menjadi solusi bagi dokter gigi dalam hal kepraktisan dan kekuatan sebagai bahan restorasi terbaru. Tujuan: Menganalisis pengaruh larutan asam laktat dan saliva buatan terhadap jumlah pelepasan ion fluor Water Settable GIC Metode: Empat puluh delapan spesimen (diameter 5 mm x ketebalan 2 mm; n= 8/kelompok dibuat dengan Water Settable GIC. Sampel yang sudah sesuai kriteria dibagi menjadi 6 kelompok. Sampel direndam selama 1 dan 7 hari didalam inkubator 37oC. Jumlah pelepasan ion fluor dibaca menggunakan alat spektrofotometer UV-VIS.Hasil: One-Way Anova hari ke-1 dan 7 menunjukkan bahwa (p<0,05) dan uji Post Hoc Bonferonni menunjukkan terdapat perbedaan yang bermakna antara semua kelompok perlakuan asam laktat hari ke-1 (10,505 ± 0,285), asam laktat hari ke-7 (11,609 ± 0,202), saliva buatan hari ke-1 (4,639 ± 0,227), saliva buatan hari ke-7 (8,723 ± 0,184), akuades hari ke-1 (3,286 ± 0,475), akuades hari ke-7 (5,778 ± 0,823). Kesimpulan: Terdapat pengaruh asam laktat dan saliva buatan terhadap jumlah pelepasan ion fluor Water Settable GIC. Kata kunci: Akuades, Asam laktat, Jumlah  pelepasan ion fluor, Saliva buatan, Water Settable GIC.